PENGARUH MODEL PEMBELAJARAN TEACHING FACTORY DAN MOTIVASI BELAJAR TERHADAP KESIAPAN BERWIRAUSAHA SISWA DI SMKN 1 MOJOANYAR: PENGARUH MODEL PEMBELAJARAN TEACHING FACTORY DAN MOTIVASI BELAJAR TERHADAP KESIAPAN BERWIRAUSAHA SISWA DI SMKN 1 MOJOANYAR - Dyah Andriati; Retno Danu Rahmawati, Prayogo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Teaching Factory learning model and learning motivation on students' entrepreneurial readiness at SMKN 1 Mojoanyar. This study uses a quantitative approach with a quasi-experimental method. The instruments used are learning motivation questionnaires and entrepreneurial readiness questionnaires. Data were collected by distributing questionnaires to grade XI students of certain expertise majors selected purposively. Data analysis was carried out using the SPSS version 27 program with a two-way ANOVA test. The results of the study indicate that: (1) there is a significant influence between the learning model on entrepreneurial readiness with a value of F = 138.793 and p = 0.000, where the Teaching Factory model is more effective than the conventional method; (2) there is a significant influence between learning motivation on entrepreneurial readiness with a value of F = 9.608 and p = 0.002; and (3) there is a significant interaction effect between the learning model and learning motivation on entrepreneurial readiness, with a value of F = 11.659 and p = 0.001. In conclusion, the Teaching Factory model and learning motivation simultaneously and interactively influence students' entrepreneurial readiness. Consequently, vocational schools need to integrate Teaching Factory into their learning and develop strategies to increase student motivation to produce young entrepreneurs who are ready to face the industrial world.